EUS-CGN versus EUS-CPN in pancreatic cancer: A qualitative systematic review. Issue 41 (15th October 2021) - Li, Mao; Wang, Zihe; Chen, Yang; Wu, Zuowei; Huang, Xing; Wu, Chao; Tian, Bole
Abstract: Background: Comparison between endosonographic ultrasonography (EUS)-guided celiac ganglia neurolysis (CGN) and EUS-guided celiac plexus neurolysis (CPN) in pain management for pancreatic cancer has engendered controversy. To analyze the effectiveness and safety of EUS-CGN and figure out whether EUS-CGN is better than EUS-CPN, a qualitative systematic review was conducted. Methods: Studies were searched from Cochrane Central Register of Controlled Trials, MEDLINE, and EMBASE up to April 2020. We only included studies with full-text and in English and assessed study quality with Newcastle-Ottawa Scale or Cochrane risk-of-bias tool. We recorded details of study design, participants, procedure performed, protocol of follow-up, pain response, quality of life, survival, and adverse events. The study was conducted under Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement 2009. Results: Five studies involving 319 patients were included. Short-term pain response rates ranged from 65.0% to 88.46% in EUS-CGN group and most studies reported its superiority over EUS-CPN. As for adverse events, the incidence of transient hypotension and gastrointestinal symptoms seemed comparable, while results of initial pain exacerbation varied among studies. Besides, EUS-CGN might provide a shorter survival. Conclusion: EUS-CGN can be safely performed while it may shorten survival. In terms of short-term pain response, EUS-CGN is better than EUS-CPN while no conclusion of long-term pain control can be drawn. Abstract : Supplemental Digital Content is available in the text